2D Electronic Spectroscopy Reveals Excitonic Structure in the Baseplate of a Chlorosome - Dostál, Jakub; Vácha, František; Pšenčík, Jakub; Zigmantas, Donatas (The journal of physical chemistry letters, 2014)
In green photosynthetic bacteria, the chlorosome baseplate mediates excitation energy transfer from the interior of the light-harvesting chlorosome toward the reaction centers. However, the electronic states of the baseplate remain unexplored, hindering the mechanistic understanding of the baseplate as an excitation energy collector and mediator. Here we use two-dimensional spectroscopy to study the excited state structure and internal energy relaxation in the baseplate of green sulfur bacterium Chlorobaculum tepidum. We resolved an exciton system with four energy states, indicating that the organization of the pigments in the baseplate is more complex than was thought before and constitutes at least four bacteriochlorophyll molecules in a close contact. Based on the finding that the energy of the baseplate states is in the same range as in the adjacent Fenna-Matthews-Olson complex, we propose a "lateral" energy transfer pathway, where excitation energy can flow through the photosynthetic unit via all the states of individual complexes.
Keywords: green sulfur bacteria; coherent 2D spectroscopy; excitons; chlorosome; energy transfer